Industrial restructuring and regional policy - Wren, Colin; Taylor, Jim (1999)
The paper examines the changing regional specialisation of UK employment over the period 1971-94, analysing the extent to which UK regional policy has altered the industrial structure of the Assisted Area regions, making them less vulnerable to economic change. All regional economies are found to have become more specialised, but industry has become less geographically concentrated leading to a convergence of regional industrial structures towards the national pattern of employment. These trends are stronger in the Assisted Areas, and have been promoted by the operation of regional policy, but the major policy effect occurs through the large-scale capital grants which have accelerated the employment decline of the traditional manufacturing industries in which the Assisted Areas were relatively over-represented. - Reproduced
Keywords: Industrial development